1996
DOI: 10.1523/jneurosci.16-03-00974.1996
|View full text |Cite
|
Sign up to set email alerts
|

Colocalization of GABA, glycine, and their receptors at synapses in the rat spinal cord

Abstract: To determine whether GABA and glycine can act as cotransmitters at synapses in the rat spinal cord, we have compared the ultrastructural distribution of GABAA-receptor beta 3 subunit with that of the glycine receptor-associated protein gephyrin and combined this with postembedding detection of GABA and glycine. We also used a dual-immunofluorescence method to confirm that gephyrin was associated with the glycine-receptor alpha 1 subunit throughout the cord. GABAA beta 3-subunit immunoreactivity was restricted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
241
0
4

Year Published

1997
1997
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 363 publications
(264 citation statements)
references
References 35 publications
19
241
0
4
Order By: Relevance
“…and rabbit polyclonal antibodies specific for ␣1 (1-9 residues), ␣4 (379 -421 residues), ␣5 (2-10 residues), ␤1 (350 -404 residues), ␤2 (351-405 residues), ␤3 (345-408 residues), ␥1 (324 -366 residues), ␥2 (319 -366 residues), and ␥3 (322-372 residues) subunits (generated by W.S.). The characterization and specificity of these antibodies have been described in detail elsewhere (Benke et al, 1991(Benke et al, , 1997Buchstaller et al, 1991;Marksitzer et al, 1993;Mertens et al, 1993;Mossier et al, 1994;Todd et al, 1996;Sperk et al, 1997). The cells were immunoreacted with guinea pig antibodies diluted 1:1000 or rabbit antibodies diluted 1:100 -300 overnight at room temperature.…”
Section: Immunoc Ytochemistr Ymentioning
confidence: 99%
“…and rabbit polyclonal antibodies specific for ␣1 (1-9 residues), ␣4 (379 -421 residues), ␣5 (2-10 residues), ␤1 (350 -404 residues), ␤2 (351-405 residues), ␤3 (345-408 residues), ␥1 (324 -366 residues), ␥2 (319 -366 residues), and ␥3 (322-372 residues) subunits (generated by W.S.). The characterization and specificity of these antibodies have been described in detail elsewhere (Benke et al, 1991(Benke et al, , 1997Buchstaller et al, 1991;Marksitzer et al, 1993;Mertens et al, 1993;Mossier et al, 1994;Todd et al, 1996;Sperk et al, 1997). The cells were immunoreacted with guinea pig antibodies diluted 1:1000 or rabbit antibodies diluted 1:100 -300 overnight at room temperature.…”
Section: Immunoc Ytochemistr Ymentioning
confidence: 99%
“…Decreased GABA A receptor clustering results in dysfunction of GABA A receptors at the cellular level and anxiety disorders at the animal level (4). Gephyrin was reported to colocalize with GABA A receptor at synaptic sites in retina and spinal cord (5,6). In GABA A receptor ␥2 subunit knockout mice, clusters of GABA A receptors were decreased greatly, and most of the gephyrin staining was also gone (7).…”
mentioning
confidence: 99%
“…In the spinal cord, there is a high degree of colocalization of glycine and GABA in neurons (Todd, 1996;Todd and Sullivan, 1990;Todd et al, 1996;Shupliakov et al, 1993;Ö rnung et al, 1996), and a matching codistribution of glycine and GABA receptors has been observed in many neurons of the spinal cord (Bohlhalter et al, 1994;Todd et al, 1996). There is evidence for a co-release of glycine and GABA, for example at the Renshaw-motoneuron synapses (e.g., Cullheim and Kellerth, 1981).…”
Section: Distribution Of Boutons Immunoreactive To the Three Amino Acidsmentioning
confidence: 99%